Online interventions for problem gamblers with and without co-occurring mental health symptoms: Protocol for a randomized controlled trial. (December 2016) - Cunningham, John; Hodgins, David; Bennett, Kylie; Bennett, Anthony; Talevski, Marina; Mackenzie, Corey; Hendershot, Christian
Abstract Background Comorbidity between problem gambling and depression or anxiety is common. Further, the treatment needs of people with co-occurring gambling and mental health symptoms may be different from those of problem gamblers who do not have a co-occurring mental health concern. The current randomized controlled trial (RCT) will evaluate whether there is a benefit to providing access to mental health Internet interventions (G + MH intervention) in addition to an Internet intervention for problem gambling (G-only intervention) in participants with gambling problems who do or do not have co-occurring mental health symptoms. Methods Potential participants will be screened using an online survey to identify participants meeting criteria for problem gambling. As part of the baseline screening process, measures of current depression and anxiety will be assessed. Eligible participants agreeing (N = 280) to take part in the study will be randomized to one of two versions of an online intervention for gamblers – an intervention that just targets gambling issues (G-only) versus a website that contains interventions for depression and anxiety in addition to an intervention for gamblers (G + MH). It is predicted that problem gamblers who do not have co-occurring mental health symptoms will display no significant difference between intervention conditions at a six-month follow-up. However, for those with co-occurring mental health symptoms, it is predicted that participants receiving access to the G + MH website will display significantly reduced gambling outcomes at six-month follow-up as compared to those provided with G-only website. Discussion The trial will produce information on the best means of providing online help to gamblers with and without co-occurring mental health symptoms. Trial registration ClinicalTrials.govNCT02800096 ; Registration date: June 14, 2016.